(3JSjjQ hGbJUGO GdeDSSI s - (3aQjhI(B, (3fQLSs ((3GdLRdFQs (3OGQ GdHGMK ddfTQ hGdGTgGQs, 2023)
(3Cge eOGQS GdacQ GdJSjjQj hGdJfXjej, GdeDSSI JYQjagG, CfhGYgG hJWhQgG, GdGOGQI hGSJQGJjLjI GdeDSSI, hXGFa GdeDSSI, hGdCfXeI GdJfSjbjI ajgG, cPdc eLOOGJ JfGaSjI GdeDSSI(B.s
Keywords: (3GdGbJUGOs; (3JSjjQ GdeDSSIs